#TITLE_ALTERNATIVE# - ASTUTI (NIM 10104084), NOVI
In this Final Project, we discuss combination labellings of graphs. A (p,q)-graph G is said a combination graph, if there a bijektive function from the vertex set {1; 2; 3; : : : ; p} such that edge values obtained by the number of combinations of the larger incident vertex value taken the smaller incident vertex value at a time are distinct. In this Final Project, we proof that web graphs are combination graphs.